A Proton‐Barrier Separator Induced via Hofmeister Effect for High‐Performance Electrolytic MnO2–Zn Batteries. Issue 16 (8th March 2022) - Yuan, Yuan; Yang, Jinlong; Liu, Zaichun; Tan, Rui; Chuai, Mingyan; Sun, Jifei; Xu, Yan; Zheng, Xinhua; Wang, Mingming; Ahmad, Touqeer; Chen, Na; Zhu, Zhengxin; et al.
Abstract: Electrolytic MnO2 –Zn batteries with economic advantages and high energy density are viable candidates for large‐scale energy storage. However, the spontaneous reactions between acidic electrolytes and Zn metal anode cause severe proton‐induced hydrogen evolution which is difficult to avoid. Herein, a proton‐barrier separator (PBS) based on poly(vinyl alcohol) (PVA) is fabricated via the Hofmeister effect for preventing hydrogen evolution. Experiments and theoretical calculations demonstrate that the concentrated sulfate enables PVA chains to form a discontinuous hydrogen bond network as well as isolated hydrophilic cavities. This unique feature can effectively obstruct proton migration to impede proton‐induced hydrogen evolution, but allow for fast Zn 2+ transfer with excellent stability. Electrolytic MnO2 –Zn batteries with PBS deliver high energy retention (91.2% after 200 cycles) and largely enhanced rate performance (20 C) in a high areal capacity of 6.67 mAh cm −2 with a very low cost ($1 m −2 ) as compared to commercial anion exchange membranes (8 C). This work sheds light on new avenues for the development of stable electrolytic MnO2 –Zn batteries by deploying PBS for preventing hydrogen evolution through a cost‐effective fabrication method, which is a universal approach that can be applied to design other stable aqueous metal‐ion batteries. Abstract : A proton barrier separator (PBS) with excellent H + blocking capabilities is developed via the Hofmeister effect, which brings bonded and caged H2 O and acetate to the poly(vinyl alcohol) chains. The PBS exhibits advantages such as fast Zn 2+ transfer, ultra‐low cost, and excellent stability, making it of great potential for applications in Zn anti‐hydrogen evolution reaction corrosion in electrolytic MnO2 –Zn batteries.